Static calculation of the bearing capacity of a two-pole membrane-rod system taking into account the air-bearing effect using the numerical Euler-Cauchy procedure - A. Yu. Kim; M. F. Amoyan; V. E. Khapilin (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The purpose of this study is to create a light, sufficiently rigid bearing coating, which can be strengthened by the air-supporting effect during overloads during force majeure. These structures can be erected in a very short time, both in combat conditions and during natural disasters. Method. The study was carried out in the software package "Program for calculating membrane-pneumatic structures by the step method using the numerical Euler-Cauchy procedure" according to the method of static calculation of membrane-pneumatic systems, taking into account non-linear factors. Result. A method for calculating air-supported double-belt membrane-rod systems for covering large spans by the iterative method of parameter increments using FEM and the Euler-Cauchy numerical procedure of the third order of accuracy has been developed. Conclusion. In design practice, the effect of strengthening the coating due to the air-supporting effect can approximately be taken equal to three. The use of the air-supported effect makes it possible to save significant funds, sometimes reaching up to 25% of the estimated cost of the structure due to the use of structural elements of a smaller section.